The Peripheral Nervous System and the Pathogenesis of Prion Diseases - Glatzel, Markus; Giger, Olivier; Braun, Nathalie; Aguzzi, Adriano (Current Molecular Medicine, 2004)
Prion diseases are inevitably fatal neurodegenerative conditions which affect humans and a wide variety of animals. Unlike other protein aggregation diseases such as Alzheimer's, Parkinson's, and polyglutamine repeat diseases, prion diseases are unique in that they are transmissible. Therefore, prion diseases are also called transmissible spongiform encephalopathies. A number of prion diseases are caused by peripheral uptake of the infectious agent. In order to reach their target, the central nervous system, prions enter their host, accumulate and replicate in lymphoid organs, and eventually spread to the central nervous system via peripheral nerves. Once the agent has reached the central nervous system, disease progression is rapid, resulting in neurodegeneration and death. In this article, we review the state of knowledge on the routes of neuroinvasion used by the infectious agent in order to gain access to the central nervous system upon entry into extracerebral sites.
Keywords: peripheral pathogenesis